Integration of Information Technology Media in Islamic Religious Education Learning as an Effort to Strengthen Students’ Religiosity in Vocational High Schools - Fadhilah, Aisyah; Budiyono, Alief (Bahasa Indonesia, Bahasa English, 2025)
This study aims to analyze the integration of information technology media in Islamic Religious Education learning as an effort to strengthen students’ religiosity. The research employs a qualitative approach with a field research method to obtain an in-depth understanding of technology-based Islamic Religious Education learning practices within a real school context. Data were collected through observations of the learning process, in-depth interviews with Islamic Religious Education teachers and students, and the examination of supporting documents such as lesson plans and students’ digital project outputs. The collected data were analyzed through data reduction, data display, and conclusion drawing. The results indicate that the integration of information technology media in Islamic Religious Education learning at vocational high schools is implemented systematically, starting from the planning, implementation, interaction, to evaluation stages of learning. Teachers utilize various digital media, including multimedia presentations, religious videos, online learning platforms, interactive quizzes, and digital projects based on Islamic values. The integration of information technology media has a positive impact on strengthening students’ religiosity, as reflected in improved religious understanding (cognitive), religious attitudes and awareness (affective), as well as religious practices and the expression of Islamic values through digital works (praxis). In addition, technology-based Islamic Religious Education learning promotes the development of Islamic digital literacy, creativity, and active student participation in the learning process.